Pengaruh Price Perception, Product Variation, dan Online Customer Experience Terhadap E-Customer Loyalty (Studi pada pengguna aplikasi online shop di Universitas Islam Malang) - Ibnusura, Esska; Rachma, N.; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abtract This study aims to determine the effect of Price Perception, Product Variation and Online Customer Experience on E-Customer Loyalty on students using online shop applications at the Islamic University of Malang. This research was conducted by distributing questionnaires online through google form to students at the Islamic University of Malang who had made repeated purchases in the last 6 months. Sample determination using purposive sampling method. The respondents collected amounted to 100, then carried out data processing using IBM SPSS Version 29 software. The results of this study state that Price Perception and Product Variation partially have no effect on E-Customer Loyalty, but Online Customer Experience has a positive and significant effect on E-Customer Loyalty. Then simultaneously affect E-Loyalty significantly and positively. Keywords : Price Perception, Product Variation, Online Customer Experience, E-Customer Loyalty